San Miguel [large type] - Boyle, T. Coraghessan (Thorndike Press, 2012)
The lives of three women on turn-of-the-20th-century San Miguel are shaped by ambition and circumstance, including the wife of a Civil War veteran who hopes to recover her health, her rebellious aspiring actress daughter and a librarian who wonders if the island's peace will endure in the face of looming war.